Fault Diagnosis in Wind Energy Management System using Extreme Learning Machine: A Systematic Review - Yaw C.T.; Teoh S.L.; Koh S.P.; Yap K.S.; Chong K.H.; Low F.W. (Institute of Physics, 2023)
Backpropagation; Electric fault currents; Energy management systems; Fault detection; Knowledge acquisition; Neural networks; Support vector machines; Wind power; Wind turbines; Back-propagation neural networks; Extreme learning machine; Fault data; Faults diagnosis; Learning machines; Real-world; Renewable energies; Renewable energy source; Support vectors machine; Systematic Review; Failure analysis